Climate Change And Respiratory Health Among School-Age Children: A Narrative Review - Tata Auliya Intan (CV. AFDIFAL MAJU BERKAH, 2026)
Climate change represents a significant global health threat, particularly for school-age children who exhibit greater physiological vulnerability. This narrative review aims to synthesize current scientific evidence on the impact of climate change on respiratory health among school-age children, covering exposure mechanisms, affected respiratory conditions, and public health implications. A literature search was conducted across PubMed/MEDLINE, Google Scholar, and ScienceDirect databases, yielding 15 articles published between 2021 and 2026 that met the pre-defined inclusion criteria. Evidence from the included studies indicates that climate change affects children's respiratory health through four primary pathways: (1) increased concentrations of air pollutants such as PM2.5 and ozone, (2) prolonged pollen seasons and elevated allergen exposure, (3) increased wildfire frequency and associated smoke exposure, and (4) extreme temperature and humidity changes. The most affected conditions include asthma, allergic rhinitis, acute respiratory infections, and pneumonia. Climate change consistently worsens respiratory health outcomes in school-age children, and integrated adaptation and mitigation policies are urgently needed, including air quality monitoring in school environments and climate-informed health education.